Anti-Radicalism Education and Strategy and Role of Islamic Religious Education in Facing Radicalism - Nurliah; Supriyanto (UII Darullughah Waddawah Pasuruan, 2024)
Radicalism refers to attitudes, views, or actions that reflect a desire to change the social, political, or cultural order drastically or fundamentally. In general, radicalism involves rejection of existing norms or the status quo in society, and is often followed by attempts to replace them with a new system that is considered more ideal. This article aims to explain education that upholds anti-radicalism as well as strategies and the role of Islamic religious education in dealing with radicalism. The method used in this research is a literature review by collecting, evaluating and synthesizing literature on similar topics so that it can provide a strong foundation for this research. This research found that anti-radicalism education is really needed in order to build a society that is tolerant, moderate and has a nationalistic attitude. Strategies that can be used in anti-radicalism education include (1) democracy education, (2) religious education, (3) social skills training, (4) critical skills training, and (5) leadership training. The important role of Islamic religious education in facing the threat of radicalism includes (1) encouraging awareness to reject radicalism, (2) encouraging social involvement, (3) strengthening the values of tolerance, (3) strengthening a calm understanding of moderate Islamic teachings, and (5) ) strengthen the values of nationalism.